2020
DOI: 10.3390/jcm9124012
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid Tumors Characteristics, Clinical Management, Active Surveillance, and Description of Our FAP Case Series

Abstract: (1) Background: desmoid tumors (DTs) are common in patients with familial adenomatous polyposis (FAP). An active surveillance approach has been recently proposed as a valuable alternative to immediate treatment in some patients. However, no clear indication exists on which patients are suitable for active surveillance, how to establish the cut-off for an active treatment, and which imaging technique or predictive factors should be used during the surveillance period. (2) Results: we retrospectively analyzed 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 73 publications
(123 reference statements)
0
16
0
1
Order By: Relevance
“…Bowel obstruction, hydroureter, hydronephrosis, and ischemic lesions are among the complications, but in severe forms, they can complicate with abscess, fistulas, gastrointestinal bleed-ing, and perforation. 3 In our case, she presented with an acute abdomen without apparent severe complications. Desmoid tumours are recognized to be the main reason for mortality in FAP patients who underwent a colectomy.…”
Section: Resultsmentioning
confidence: 59%
“…Bowel obstruction, hydroureter, hydronephrosis, and ischemic lesions are among the complications, but in severe forms, they can complicate with abscess, fistulas, gastrointestinal bleed-ing, and perforation. 3 In our case, she presented with an acute abdomen without apparent severe complications. Desmoid tumours are recognized to be the main reason for mortality in FAP patients who underwent a colectomy.…”
Section: Resultsmentioning
confidence: 59%
“…Consequently, the disease is easily misdiagnosed as soft tissue sarcoma[ 18 ]. Sanchez-Mete et al [ 19 ] pointed out that soft tissue sarcoma grows rapidly, insufficient blood supply inside the tumor can cause necrosis, and the focus shows expansive growth, compressing the surrounding tissue. Therefore, sarcoma has a clear boundary, while osteofibroma has less necrosis and the invasive growth results in the lack of a clear boundary between the tumor and surrounding tissue; additionally, a band of low signal intensity on T1WI and T2WI can be seen.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal treatment for DTs in FAP patients has not been established due to a lack of sufficient cases. For more than 30 years, major hospitals around the world have reported on the diagnosis and treatment of FAP-associated DTs [9][10][11][12][13][14][15][16][17][18][19]. Based on these findings, we recently reported data on DTs from Japan as well [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 90%
“…Several studies [10,11,26,27] reported that DTs develop in about 10%-25% of FAP patients and may be the leading cause of death among those who have undergone colectomy [1]. Table 1 presents the summary of the prevalence of DTs according to previous reports [9][10][11][12][13][14][15][16][17][18][19] from world-famous facilities, including the Japanese Society for Cancer of the Colon and Rectum (JSCCR) registry and Japanese single institutes [20][21][22]. The prevalence was 7%-38%, but when the number of patients was more than 100, it was about 7%-20%, which was consistent across the reported years.…”
Section: Prevalence Of Dts In Fap Patientsmentioning
confidence: 98%